18: Perceived Utility of Respiratory Virus Testing for Febrile Infants Under Six-Weeks of Age Among Canadian Pediatric Emergency and Inpatient Physicians. Issue 5 (1st June 2015) - Burnstein, B; Quach, C; Dubrovsky, AS
Abstract: BACKGROUND: Well appearing febrile infants with viral illnesses cannot be easily distinguished from those with occult life-threatening infections by history and physical exam alone. OBJECTIVES: This national practice variation study sought to assess current approaches to febrile infants under 6-weeks of age, and determine how management is influenced by respiratory virus testing. DESIGN/METHODS: A scenario-based survey describing two hypothetical cases of febrile infants without a focus aged 3- and 5-weeks was sent to ED and inpatient physicians at all of the 15 tertiary pediatric centers across Canada. Participants were asked multiple-choice questions regarding management decisions with and without results of respiratory virus testing. χ 2 testing was used to compare proportions. RESULTS: Response rate was 78% (n=329; 190 ED physicians, 139 inpatient physicians). Investigations most commonly performed for both 3- and 5-week old infants were urine culture, urine analysis, CBC and blood culture. Lumbar puncture was performed less frequently in 5-week old infants (49% vs. 93%, P<0.0001). Conversely, respiratory virus testing was performed more frequently among 3-week old infants (46% vs. 34%, P<0.05). Older infant age decreased rate of admission, however detection of a respiratory virus further reduced admissions among both 3-week (83% vs. 95%, P<0.001) and 5-week old infants (36% vs. 52%, P<0.001). Similarly, empiric antibiotic treatment was initiated less frequently in older infants, and was further reduced by detection of a respiratory virus among both 3-week (65% vs. 92%, P<0.001) and 5-week old infants (25% vs. 39%, P<0.001). Inpatient physicians were more likely than ED physicians to admit (68% vs. 41%, P<0.001) and start antibiotic therapy (52% vs. 30%, P<0.001) in 5-week old infants. Among inpatient physicians, 81% would discharge 5-week old infants in ≤24 h with a detectable respiratory virus and otherwise negative workup; whereas admission duration among 3-week old infants was highly variable. CONCLUSION: The management of febrile infants under 6-weeks differs between ED and inpatient physicians, and by infant age. Respiratory virus testing could potentially reduce admissions and empirical antimicrobial treatment, as well as permit earlier discharge. Establishment of clinical guidelines for this patient population is warranted.